A Study On GJB2 And GJB6 Gene Mutations Among Malays With Non-Syndromic Hearing Loss - Zainal, Siti Aishah (2010)
Hearing loss is the most common congenital sensory defects in human. About one in a thousand newborn in the world is born with the abnormality, which may vary from mild level of hearing loss to profound loss. This loss can be caused by two factors, genetic and environmental factors and more than 50% of the defect is due to genetic causes. It has been proven that multi genes are involved in non-syndromic hearing loss (NSHL), a type of hearing loss without other symptoms and covered in this study. Mutations in GJB2 gene have been shown to be a major role for congenital NSHL.